Referenciais freireanos para a construção de um currículo crítico-transformador em um curso de gestão tributária - Cunha, Maurício Lopes da (2024)
This research aims to find principles of a critical-transformative curriculum to reorient a Lato Sensu Postgraduate course in Tax Management. The work was supported by Paulo Freire’s framework, providing that it brings the utopia of humanization, with the perspective of social transformation with more solidarity, democracy and social justice. Alongside Paulo Freire, the theoretical framework is also based on the contribution of authors from the fields of critical education (Ira Shor, Michael Whitman Apple, José Gimeno Sacristán and Jurjo Torres Santomé) and tax management (Hilário Franco, Sérgio de Iudícibus, José Carlos Marion and Antonio Lopes de Sá). To answer the research question “What is the contribution of Paulo Freire's framework to the construction-reconstruction of a critical-transformative curriculum in tax management?”, we worked with a qualitative approach, and data production was accomplished via document analysis of the course and the results of interviews carried out with course graduates. As a result, we suggest principles, within the framework of critical education, capable of guiding the construction-reconstruction of a new curriculum for the aforementioned course, from a critical-transformative perspective